Síntese hidrotermal de biochar derivado de cascas de banana prata (Musa acuminata Cavendish) para utilização em eletrodos de supercapacitor - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The growing demand for electrical energy resulting from the increase in the consumption of electrical devices, both on a civil and industrial scale, has made countless scientists turn their eyes to research in energy generation and storage. Parallel to this, the concern with the generation of residues, triggered research where industrial residues of carbonaceous origin began to be widely studied. In this research, banana peels were used as raw material to obtain biochar, which was later activated with potassium hydroxide and iron III chloride to obtain a greater specific surface area, for application in supercapacitor electrodes. The data expressed here correspond to the morphological, EDS and electrochemical data of the bichar activated with iron III chloride and potassium hydroxide in the mass proportions 1:1 and 1:2 biomass:activating agent in electrolyte solutions of 1 Mol.L-1 sodium sulfate and potassium hydroxide 1 Mol.L-1.
Keywords: Carvão vegetal; CIENCIAS EXATAS E DA TERRA; CIENCIAS EXATAS E DA TERRA: QUIMICA: FISICO-QUIMICA: ELETROQUIMICA; Biochar; Banana; Ativação